Anti-relapse medications: Preclinical models for drug addiction treatment - Yahyavi-Firouz-Abadi, Noushin (2009)
Addiction is a chronic relapsing brain disease and treatment of relapse to drug-seeking is considered the most challenging part of treating addictive disorders. Relapse can be modeled in laboratory animals using reinstatement paradigms, whereby behavioral responding for a drug is extinguished and then reinstated by different trigger factors, such as environmental cues or stress. In this review, we first describe currently used animal models of relapse, different relapse triggering factors, and the validity of this model to assess relapse in humans. We further summarize the growing body of pharmacological interventions that have shown some promise in treating relapse to psychostimulant addiction. Moreover, we present an overview on the drugs tested in cocaine or methamphetamine addicts and examine the overlap of existing preclinical and clinical data. Finally, based on recent advances in our understanding of the neurobiology of relapse and published preclinical data, we highlight the most promising areas for future anti-relapse medication development.